The influence of changes in hospital drug formulary on the prescription of proton pump inhibitors - Raquel Vázquez-Mourelle; Eduardo Carracedo-Martínez (Farmacia Hospitalaria)
Objective: To analyze the impact of introducing omeprazole in the drug formulary of the Hospital de Barbanza on prescriptions made in hospital and out-of-hospital (Outpatient Units and Primary Care) for all Proton Pump Inhibitors (PPIs). Material and methods: A 36-month retrospective descriptive study in a level I hospital. The basic units of work are Dose-Population- Day in the outpatient setting, and the Defined Daily Dose/stays-day for hospitalized patients; the proportion of DDDs for omeprazole vs. the rest of PPIs is used as measure of efficiency. For statistical analysis, we built a segmented regression model. Results: In the outpatient units, there are statistically significant changes for pantoprazole and rabeprazole. The first drug, which was stable before the intervention, suffered an immediate decrease; rabeprazole, which was increasing before the intervention, presented a subsequent downward trend. In Primary Care, a statistically significant change was confirmed for pantoprazole, with a long-term decreasing trend. In hospitalization, statistically significant changes were observed for pantoprazole and omeprazole; the first one with an immediate decrease and a long-term tendency to decrease, while omeprazole experienced an immediate increase and long-term growth. The evolution of the omeprazole percentage vs. all PPIs showed increases in all three scenarios. Conclusions: A shift to a more efficient prescription of PPIs was observed in all healthcare settings following the introduction of omeprazole in the hospital drug formulary. The inclusion of efficient drugs, or the removal of those inefficient, can be a potentially useful tool in order to improve prescription profiles.